Rethinking Muhammadiyah: Masjid, Teologi Dakwah Dan Tauhid Sosial (Perspektif Filsafat Dakwah) - H. Abror, Robby (Jurnal Ilmu Dakwah, 2012)
As a dakwah movement that has a social ideals to bring the genuine Islamic community is the basic philosophical of Muhammadiyahâs movement. There are three important concepts such as, the movement of jamaâa, qaryah tayyibah and sakinah family. Then came the strategy of "cultural daâwah" and look at the reality of the importance of greeting compound. In addition, the need to emphasize the contemporary missionary preaching bi al-kitÃ¢bah, in addition to bi-lisÃ¢n al-hÃ¢l. Brilliant thinking regarding the function and existence redefined mosque, theology, preaching and social monotheism is needed to revitalize the spirit of the mission within the framework of philosophical-rational.